1996
DOI: 10.1136/thx.51.11.1162
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy following a single lung transplant.

Abstract: (CMV) in the pulmonary tissue ofpatients with AIDS8 and human herpes virus 6 associated interstitial pneumonitis in bone marrow transplant patients.9 Although a number of features of this suggest that EBV may be pathogenic, it is important to note that, because of the presence of immunosuppression, it remains possible that the EBV replication was coincidental rather than causal to the graft failure.The histological features of the open lung biopsy specimen suggest that neither obliterative bronchiolitis nor br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Following the first report of a successful pregnancy in 1996 [ 2 ], there have been several reports of successful pregnancies after lung transplantation [ 1 , 3 – 9 ]. Registries have been established to collect data regarding pregnancy after organ transplant, the National Transplantation Pregnancy Registry being established in the USA in 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Following the first report of a successful pregnancy in 1996 [ 2 ], there have been several reports of successful pregnancies after lung transplantation [ 1 , 3 – 9 ]. Registries have been established to collect data regarding pregnancy after organ transplant, the National Transplantation Pregnancy Registry being established in the USA in 1991.…”
Section: Discussionmentioning
confidence: 99%
“…At this time their risk for developing obliterative bronchiolitis can be assessed, as this is a serious long term complication of lung transplantation. There is little information whether pregnancy increases the risk of developing obliterative bronchiolitis 41. Such patients should have regular lung function tests and flow volume loop recorded, a reduction in expiratory flow at low lung volumes being a sensitive marker of obliterative bronchiolitis.…”
Section: Lung Transplant Patients41mentioning
confidence: 99%
“…Most reports of pregnancies in lung recipients have been single center case studies. [16][17][18] The purpose of this study was to analyze outcomes of pregnancies in female lung recipients reported to the NTPR.…”
mentioning
confidence: 99%